Kirtland Cutter : architect in the land of promise - Matthews, Henry (University of Washington Press in association with Eastern Washington State Historical Society, 1998)
In the early years of the twentieth century, Spokane was singled out for praise in the West for the quality of its architecture and the impressive way it had rebuilt after the devastating fire of 1889. Major credit for the city's distinctive character was extended to Kirtland Kelsey Cutter for his "rare architectural force and genius for design." His remarkable career, stretching from the Gilded Age to the Great Depression, allows a fascinating study of the evolution of an eclectic form of architecture that was an inevitable response to rich regional and historical influences during a time of transition from frontier settlements to modern city--Publisher description.